2020
DOI: 10.1111/trf.15669
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage time prolongation on in vivo and in vitro characteristics of 4°C–stored platelets

Abstract: BACKGROUND Cold (4°C)‐stored platelets are currently under investigation for transfusion in bleeding patients. It is currently unknown how long cold‐stored platelets can be stored for clinical applications. STUDY DESIGN AND METHODS Twenty three subjects were recruited. Twenty‐one subjects were available for in vivo assessment and received indium‐111 radiolabeled, cold‐stored platelets. We investigated 5‐ (n = 5), 10‐ (n = 6), 15‐ (n = 5), and 20‐day–stored (n = 5) platelets and obtained samples for in vitro te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 37 publications
8
49
0
Order By: Relevance
“…In general, the observed changes to the platelet parameters were progressive in both RT and cold groups, but occurred at a slower rate in the cold-stored platelets. As previously shown, cold-stored platelets remained metabolically active throughout 21 days of storage, 5,15,[23][24][25] whereas glycolytic metabolism stalled in the RT-stored platelets in PAS by day 14. In contrast, residual glucose from 40% plasma was sufficient for 3 weeks when cold-stored, and PAS prevented acidification of the component.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In general, the observed changes to the platelet parameters were progressive in both RT and cold groups, but occurred at a slower rate in the cold-stored platelets. As previously shown, cold-stored platelets remained metabolically active throughout 21 days of storage, 5,15,[23][24][25] whereas glycolytic metabolism stalled in the RT-stored platelets in PAS by day 14. In contrast, residual glucose from 40% plasma was sufficient for 3 weeks when cold-stored, and PAS prevented acidification of the component.…”
Section: Discussionmentioning
confidence: 82%
“…However, it is prudent to keep in mind that the pH is only a surrogate marker of platelet quality, and it remains contentious as to whether it is predictive of clinical outcomes. 41,42 While it is well established that cold-storage is associated with reduced in vivo viability, 1,25,43 these indicators appear to be further affected by the composition of the storage solution. 11,12,25 Stolla et al, has recently demonstrated that in healthy human volunteers, in vivo platelet recovery was lower after storage for 10 days when platelets were supplemented with PAS (PAS-C and PAS-F), compared to platelets stored in plasma; however, the survival between the platelets in each group was similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stolla et al 44 found that cold‐stored PLTs have a progressive decline in their survival upon autologous transfusion in humans within the first 10 days of storage with even further decline in the first 24‐hour recovery when they are cold stored for up to 20 days. Clustering of GPIbα on the PLT surface was noticed following refrigeration of PLTs 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The current practice of storing PLTs at a room temperature of 22°C resulted from studies that demonstrated optimized circulating time and increase in PLT count in oncology patients but may not maximize or preserve PLT function 12 . Alternative methods to PLT and whole blood storage are being investigated and used—including cold storage (4°C) 13,14 …”
Section: Discussionmentioning
confidence: 99%